Promoting Self-Advocacy Among Older Adults: Lessons From Boston's Senior Civic Academy. (April 2021) - Bui, Cindy N.; Coyle, Caitlin E.; Freeman, Alison
Fostering ways for older residents to be civically engaged is one dimension of an age-friendly community. While research on civic engagement among older adults often focuses on volunteering, this study focuses on advocacy and political involvement as another important form. The Age-Friendly Boston Initiative developed the Senior Civic Academy (SCA) program as a self-advocacy course that simultaneously educates older residents about policy-making processes and engages them in advocacy training to incorporate their voices in local policy and planning. This study details the formative evaluation of the SCA, and utilizes mixed methods to evaluate the program's impact on the participants ( N = 49). Lessons learned from the SCA serve as a guide for other communities to develop programs that encourage civic engagement and advocacy among older adults.